The Impact of the Electoral System on the Performance of the Legislative Authority - Al Ansari, Khaled; Dala, Sam (Journal of Legal Sciences, 2026)
This research deals with the relationship between the electoral system" used in the country and its impact on the efficiency and effectiveness of the legislative authority. Explain how the electoral system affects the quality of representation in Parliament and the legislative and oversight performance of the Representative Council. The research aims to analyze the types of electoral systems and evaluate their impact on the efficiency of the legislative authority. In this study, we followed the descriptive and comparative approach. The research included the main topics represented by the theoretical framework of electoral systems and their types, the most common of which are the majority system and the proportional representation system’s. W, with a statement of the expected results of these systems in terms of their impact on the legislative authority.